Bid Costs and the (In)efficiency of Public Procurement Auctions - Niels Blomgren-Hansen (Copenhagen Business School (CBS), Department of Economics, 2019)
The paper analyzes the excess entry hypothesis for sealed-bid first price public procurement auctions.The hypothesis is proved analytically for any feasible combination of bid preparation cost and bid evaluation cost when the bidders face a rectangular cost density function and confirmed in numerical simulations based on a family of flexible cost density functions. The excess entry hypothesis implies that the procurer may reduce both his own cost and the social cost by imposing a positive fee on the bids. Sequential search is a superior strategy to a public procurement auction whether or not the procurer imposes an optimal fee on the bids.
hdl:10398/9710
Keywords: D21; D43; D44; L13; L51; 330; Excess entry; Public procurement auctions; Optimal fee; Sequential search